Pengaruh Metode Mentorship Perawat Terhadap Kemampuan Caring Mahasiswa - Maria Magdalena Setyaningsih; Sr. Felisitas; Maria Prieska Putri P. A (Akademi Keperawatan Dharma Husada Kediri, 2016)
Initial study conducted by the researcher on nurse students undertaking clinical practice shows that the nurse students are not yet competent in nursing care. Previous study conducted by Setyaningsih and Sutiyarsih (2015) shows that 47.6% of nurses have enough ability to guide nurse students. In response to the current facts and phenomena, a method of mentorship may be a breakthrough for the nurse candidates to achieve nursing competence. The purpose of this study is to discover how how mentorship affects nurses in terms of the AKPER X students’ capability in nursing care at RS x. This is an experimental study using post test only study design. A sample of 31 students at AKPER X was used by using purposive sampling technique. Data analysis is done through product moment correlation test proceeded with linear regression analysis. Research shows that 100% of the nurses are able to conduct mentorship, 100% of the students have caring capability. The result of the product moment correlation test shows that there is positive correlation between the two variables , and the result of linear regression analysis shows the effect of nurse mentorship on students’ capability of nursing care. Analysis of the results of the study indicates that the main factor that affects the nurse mentorship is the age, while the main factor that affects students’ nursing care ability is age and sex. Based on the study result, researchers suggests that Hospital management improve the mentors’ competence in guiding students. Key words : mentorship, nurses, caring capability, students